RESEARCH TRENDS IN ACADEMIC PROCRASTINATION IN STUDENTS - Muti'ah, Aulia; Annisa, Zakiyyah; Puspita, Eka; Haikal Afifsyah, Ahmad; Alferi, Alrefi (Program Studi Bimbingan dan Konseling FKIP UNJA, 2024)
Academic procrastination is procrastination behavior that is carried out deliberately without considering the priorities that must be worked on in the academic realm. The aim of this research is to analyze the research direction of the academic procrastination variable over the last 9 years. This research method uses content analysis with samples taken from articles published on the sciencedirect, researchgate and google scholar websites. The findings of this research show that academic procrastination has internal and external factors, and has an influence on personal and learning areas. The most widely used research method is quantitative correlational. It is hoped that academic procrastination research can contribute to future researchers who wish to research academic procrastination with more varied aspects and methods.